A realistic approach to information services on mobile apps. Issue 1 (2nd January 2017) - Adrakatti, Arun F.; Mulla, Kamalasab R.
ABSTRACT: The deployment of information services through mobile apps is an innovative plan to provide effective services to end users. Libraries can promote and expand their existing information services by offering mobile apps to access electronic resources, the library Web site, online catalogs, and institutional repositories. This article discusses a realistic approach to enhance library services through mobile applications. The present study focuses on mobile applications adopted in the library of Gogte Institute of Technology. It also discusses the working module, features, and framework of mobile apps.